Is Depression Associated with the Risk of Cardiovascular Disease or Vice Versa? - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
The comorbidity between cardiovascular disease (CVD) and depression has been observed for many years. Several biological and behavioral hypotheses have been proposed to explain this comorbidity. However, the underlying common mechanisms are still unclear. Evidence suggests a bidirectional relationship between depression and CVD. Inflammation has been implicated in the etiology of both depression and CVD. In this review, we aim to increase awareness for CVD and depression comorbidity and provide some insights about the possible role of inflammation.
Keywords: major depression; cardiovascular disease; inflammation; hs-CRP; C-REACTIVE PROTEIN; ACUTE MYOCARDIAL-INFARCTION; ISCHEMIC-HEART-DISEASE; ANTIDEPRESSANT TREATMENT; IMMUNE-SYSTEM; INFLAMMATION; HEALTH; METAANALYSIS; MARKERS; ATHEROSCLEROSIS